THE DEVELOPMENT OF BIRACIAL IDENTITY IN PATRICIA PARK’S RE JANE - Ade Nine Suryani; Nur - Saktiningrum (Universitas Gadjah Mada, 2022)
Race in America is an important issue because, through the decennial census, the American government distributes the federal budget to many communities to support their education and health. Throughout the American census history, the government starts to acknowledge the people with one or more races in 2000. However, in society, people with more than one race will be classified based on their physical features and acknowledged by only one race. This research aims to reveal the biracial identity development in Re Jane novel by Patricia Park (2015) using racial identity and negotiation theory. It uses a qualitative method with primary data source from the novel and secondary data source from books, thesis, journals, articles, and online sources. This research shows that factors that affect Jane’s biracial Korean-American identity development are microlenses factors consisting of inherited influences and social environment. These factors make Jane not have a sense of belonging both in the the Korean-American community and the Caucasian community. Second, to have a sense of belonging in the community, she negotiates with her family, friends, and workplace by supporting and challenging others’ desired self-image. Thus she can feel secure, trusted, and accepted.